A minimally invasive strategy to evacuate hematoma by synergy of an improved ultrasonic horn with urokinase: An in vitro study. Issue 3 (31st January 2022) - Tang, Junhui; Tang, Jiawei; Zhu, Qiong; Liao, Yiyi; Bai, Luhua; Luo, Tingting; Feng, Shuang; Liu, Zheng
Abstract: Objectives: In this study, Ultrasound Needle—an improved minimally invasive ultrasonic horn device was used to explore its potential of synergizing with urokinase in enhancing clots lysis in an in vitro intracranial hematoma model. Materials and methods: Ten milliliter bovine blood was incubated for 3 h at 37℃, and coagulated into clot to mimic intracranial hematoma in vitro. Ultrasound Needle was an improved ultrasonic horn with a fine tip (1.80 mm) and metallic sheath, and had a frequency of 29.62 kHz. The 10, 000 IU urokinase was injected through the metallic sheath during the vibration of Ultrasound Needle tip to lyse the clots for 8 min under different working parameter settings ( n  = 8) to explore the influence of parameters Amplitude (%) and Duty (%) on clot lysis weight ( W 0 ). The maximum temperatures were measured by an infrared thermometer during the treatment process. The W 0 of different treatment groups (US (Ultrasound Needle), US + NS (normal saline), UK (urokinase), US + UK, n  = 8) were compared to verify the synergistic lysis effect of Ultrasound Needle combined with urokinase at optimal working parameters (40% Amplitude, 20% Duty; input power 4.20 W; axial tip‐vibration amplitude 69.17 μm). Clots samples after treatment were fixed overnight for macroscopic examination. And fluorescent frozen sections and scanning electron microscopy examination were performed to show microscopic changes in clots and evaluate the cavitation effect of Ultrasound Needle on promoting drug diffusion within the clots. Results: The clot lysis weight W 0 increased with the parameters Amplitude (%) and Duty (%), reached a peak (2.435 ± 0.137 g) at 40% Amplitude and 20% Duty (input power 4.20 W), and then decreased. Higher Amplitude (%) and Duty (%) led to higher maximum temperature, and W 0 was negatively correlated with the maximum temperature after the peak ( r  = −0.958). At the optimal parameter setting, the maximum temperature was 33.8 ± 0.9℃, and the W 0 of the US + UK group was more than four times of UK alone group (2.435 ± 0.137 g vs. 0.607 ± 0.185 g). Fluorescent frozen sections confirmed that the ultrasound energy of Ultrasound Needle could mechanically damage the clot tissues and promote the intra‐clots drug diffusion. Macroscopic examination showed that US + UK group caused larger clots lysis area than UK alone group (2.08 cm 2 vs. 0.65 cm 2 ). In addition, electron microscopy examination exhibited that the fibrin filaments of the clots in US + UK group were lysed more thoroughly compared to single treatment groups. Conclusions: Ultrasound Needle, an improved ultrasonic horn device, can mechanically damage the clot tissues and exhibit an excellent synergistic lysis effect with thrombolytic drugs. Therefore, Ultrasound Needle has great potential in providing a new minimally invasive strategy for rapid intracranial hematoma evacuation.